Neurological worsening in Wilson disease - clinical classification and outcome - Mohr, Isabelle; Pfeiffenberger, Jan; Eker, Ecem; Merle, Uta; Poujois, Aurélia; Ala, Aftab; Weiss, Karl Heinz (Journal of hepatology, 2023)
Background & Aims - Prevention of neurological worsening (NW) under therapy is an unmet need in the management of Wilson disease (WD). In this study, we aimed to characterize the occurrence, associated outcomes and potential reversibility of NW in WD. - Methods - From a total cohort of 457 patients with WD, 128 patients with WD and neurological features at any time point (all Caucasian, 63 females, median age at diagnosis 22 years) were identified by chart review at University Hospital Heidelberg and grouped according to initial presentation. The timing and occurrence of NW was assessed following a structured clinical examination during clinical visits. - Results - Early NW (within the first 3 months of therapy) was observed in 30 out of 115 (26.1%) patients with neurological or mixed presentation and never in patients with a purely hepatic or asymptomatic presentation (0%). Late NW (after >12 months) was seen in a further 23 (20%) with neurological or mixed presentation and in 13 out of 294 (4.4%) patients with a hepatic or asymptomatic presentation. The median time from start of treatment to late NW was 20 months. Only three patients experienced NW between 3 and 12 months. NW was observed with D-penicillamine, trientine and zinc therapy and was reversible in 15/30 (50%) with early NW and in 29/36 (81%) with late NW. - Conclusions - In this study, we identified two peaks in NW: an early (≤3 months) treatment-associated peak and a late (>12 months of treatment) adherence-associated peak. Early paradoxical NW was attributed to treatment initiation and pre-existing neurological damage, and was not observed in those with a hepatic or asymptomatic presentation. Late NW is likely to be associated with non-adherence. - Impact and implications - In patients with Wilson disease, defined as an excess accumulation of copper which can damage the liver, brain and other vital organs, neurological worsening can occur despite chelation therapy. The study identifies different patterns of ‘early’ (<3 months) vs. ‘late’ (>12 months) neurological worsening in relation to initiation of chelation therapy and establishes possible causes and the potential for reversibility. These data should be useful for counseling patients and for guiding the optimal management of chelation therapy.